Comparison at the sub-100 fW optical power level of calibrating a single-photon detector using a high-sensitive, low-noise silicon photodiode and the double attenuator technique. (8th July 2016) - Porrovecchio, G; Šmid, M; López, M; Hofer, H; Rodiek, B; Kück, S
Abstract: A comparison down to sub-100-fW optical power level was carried out between a low-noise Silicon photodiode and a low optical flux measurement facility based on a double attenuator technique. The comparison was carried out via a silicon single-photon avalanche diode (Si-SPAD), which acted as transfer standard. The measurements were performed at a wavelength of 770 nm using an attenuated laser as a radiation source at optical power levels between approximately 86 fW and approximately 1325 fW, corresponding to approximately 330 000 photons s −1 and approximately 5.2  ×  10 6 photons s −1, respectively. The mean relative deviation of the detection efficiencies of the Si-SPAD, determined by the Si-photodiode and the low optical flux measurement facility, i.e. between two completely independent traceability routes, was  <  0.2%, thus well within the combined standard uncertainty of the two measurements. To our knowledge, this is the first comparison for the detection efficiency of a single photon detector using a direct optical flux measurement by a conventional Si-photodiode at such low power levels.